2018
DOI: 10.1002/14651858.cd004414.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing occupational irritant hand dermatitis

Abstract: Moisturisers used alone or in combination with barrier creams may result in a clinically important protective effect, either in the long- or short-term, for the primary prevention of OIHD. Barrier creams alone may have slight protective effect, but this does not appear to be clinically important. The results for all of these comparisons were imprecise, and the low quality of the evidence means that our confidence in the effect estimates is limited. For skin protection education, the results varied substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 108 publications
0
34
0
7
Order By: Relevance
“…Education and adherence behavior should begin in academic institutions because they are optimal environments to encourage good habits [4], since knowledge among nurses and students seems to be deficient [42], maybe due to some barriers such as allergic reactions, lack of staff, or lack of awareness [43,44,45,46]. Although traditional methods provide the necessary notions for the development of practical skills, they do not ensure the acquisition of knowledge [47].…”
Section: Discussionmentioning
confidence: 99%
“…Education and adherence behavior should begin in academic institutions because they are optimal environments to encourage good habits [4], since knowledge among nurses and students seems to be deficient [42], maybe due to some barriers such as allergic reactions, lack of staff, or lack of awareness [43,44,45,46]. Although traditional methods provide the necessary notions for the development of practical skills, they do not ensure the acquisition of knowledge [47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to the use of protective wear and reduction in occupational irritancy and allergen exposure, increasing awareness on the importance of a competent skin barrier in the workplace and strategies aimed at avoidance of skin barrier damage is essential in the prevention of occupational skin diseases . A recent Cochrane review reported that moisturizers used alone or in combination with barrier creams may have a clinically important protective effect for the primary prevention of occupational CD . In line with the conclusions of that review, use of moisturizers has been recommended by the European Society of Contact Dermatitis in their recent guidelines for the prevention and therapy of occupational hand dermatitis .…”
Section: Impaired Skin Barrier As a Risk Factor For Contact Dermatitismentioning
confidence: 92%
“…[33] • Apply an ointment-based emollient during work time after hand washing and after work, at home, to support the regeneration of the skin barrier. [35] • Consider wearing a cotton liner under gloves to prevent irritation from sweat if wearing for extended periods of time. [36] Face…”
Section: Author Contributionsmentioning
confidence: 99%